The Influence of Green Industry and Environmental Corporate Social Responsibility on Business Sustainability in Improving Company Business Performance - Bagaskhara, Reyzza Anferditya; Saragi, Naomi Jesika; Palalangan, Reza; Hidayati, Retno; Lataruva, Eisha (Economic and Business Horizon, 2025)
The research is an Empirical Study on Food Manufacturing, investigates the influence of green industry and environmental on business sustainability and company performance. Using the RBV as framework, this study examines how green industry and environmental CSR can enhance company performance and sustainability by reducing environmental impact and fostering stakeholder value. The study focuses on medium to large food manufacturing companies in Central Java, with key variables including business sustainability, green industry implementation, and environmental CSR. It aims effects on business performance. This methodology includes data gathered from primary and secondary. Understanding how sustainable practices impact business performance and provides insights into the practical implementation of green industry principles and CSR for improved operational efficiency, business longevity, and social responsibility.